Community knowledge, perceptions and attitudes regarding leprosy in rural Cameroon: The case of Ekondotiti and Mbonge health districts in the South-west Region - Tabah, Earnest Njih; Nsagha, Dickson Shey; Bissek, Anne-Cécile Zoung-Kanyi; Njamnshi, Theophilus Ngeh; Njih, Irine Ngani-Nformi; Pluschke, Gerd; Njamnshi, Alfred Kongnyu (PLOS Neglected Tropical Diseases, 2018)
Author summary Leprosy is one of the oldest diseases known to humanity but remains largely misunderstood. This misunderstanding leads to stigma towards people with leprosy (PWL). We explored knowledge, perceptions and attitudes regarding leprosy among 233 community members in the South-west of Cameroon. Our respondents were very familiar with leprosy. Their information on leprosy was mainly from community volunteers, friends or from the media. Despite high familiarity, very few knew the cause of leprosy. A good proportion attributed it to curses, unclean blood, or heredity. However, most of them agreed that leprosy was curable and would advise medical treatment. Attitudes of community members towards PWL were generally negative. Very few of them would shake hands with, eat from the same plate, or allow their child to play with or marry a PWL. The main reasons for these negative attitudes were the beliefs that leprosy is a curse; is caused by a germ; and having seen a leprosy patient. An awareness campaign using community volunteers and the media, with information on the cause of leprosy, its clinical manifestations and curability could improve community knowledge and attitudes towards leprosy. This would ultimately contribute to the reduction of leprosy burden in the community.